Metabolic pathways that permit Mycobacterium avium subsp. hominissuis to transition to different environments encountered within the host during infection - Abukhalid, Norah; Rojony, Rajoana; Danelishvili, Lia; Bermudez, Luiz E. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction M. avium subsp. hominissuis (M. avium) is an intracellular, facultative bacterium known to colonize and infect the human host through ingestion or respiratory inhalation. The majority of pulmonary infections occur in association with pre- existing lung diseases, such as bronchiectasis, cystic fibrosis, or chronic obstructive pulmonary disease. M. avium is also acquired by the gastrointestinal route in immunocompromised individuals such as human immunodeficiency virus HIV-1 patients leading to disseminated disease. A hallmark of M. avium pulmonary infections is the ability of pathogen to form biofilms. In addition, M. avium can reside within granulomas of low oxygen and limited nutrient conditions while establishing a persistent niche through metabolic adaptations. Methods Bacterial metabolic pathways used by M. avium within the host environment, however, are poorly understood. In this study, we analyzed M. avium proteome with a focus on core metabolic pathways expressed in the anaerobic, biofilm and aerobic conditions and that can be used by the pathogen to transition from one environment to another. Results Overall, 3,715 common proteins were identified between all studied conditions and proteins with increased synthesis over the of the level of expression in aerobic condition were selected for analysis of in specific metabolic pathways. The data obtained from the M. avium proteome of biofilm phenotype demonstrates in enrichment of metabolic pathways involved in the fatty acid metabolism and biosynthesis of aromatic amino acid and cofactors. Here, we also highlight the importance of chloroalkene degradation pathway and anaerobic fermentationthat enhance during the transition of M. avium from aerobic to anaerobic condition. It was also found that the production of fumarate and succinate by MAV_0927, a conserved hypothetical protein, is essential for M. avium survival and for withstanding the stress condition in biofilm. In addition, the participation of regulatory genes/proteins such as the TetR family MAV_5151 appear to be necessary for M. avium survival under biofilm and anaerobic conditions. Conclusion Collectively, our data reveal important core metabolic pathways that M. avium utilize under different stress conditions that allow the pathogen to survive in diverse host environments.